East European U3As facing the problem of seniors’ needs (Revista Lusófona de Educação, 2021)
The development of Universities of the Third Age in Central and Eastern Europe progressed in a specific manner, and was only partially inspired by the changes occurring in adult education in other parts of the world. Affected by various historical determinants in this part of Europe, a specific model of the U3A was created, embracing holistic and flexible education. This article presents the results of research into the various needs of U3A students in Poland, Belarus and Ukraine. Selected needs were analysed, as well as how they manifest themselves in each of those countries. The research was conducted by interview-questionnaire on 515 U3A students during 2015-6. The research results show that the developmental needs of U3A students are different in different countries. It could also be presumed that the holistic model of the U3A works well in various cultural environments and under varied conditions.Key words: U3A; senior aging society; gerontology, seniors’ needs; educational needs